2015
DOI: 10.21608/fjard.2015.191766
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Stress and Foliar Feeding With Boron and Zinc Under NPK Fertilizer Levels on Growth and Yield of the New Promising Cotton Genotype (Giza 86 X 10229)

Abstract: Two field experiments were carried out at Sakha Agricultural Research Station at Kafr El-Sheikh Governorate, Egypt, on new promising cotton genotype (Giza 86 X 10229) during 2013 and 2014 seasons to study the effect of water stress and foliar feeding with boron and zinc under NPK fertilizer levels on growth, earliness, yield, yield components and some fiber quality. Each experiment was laid out in a split split-plot design with four replications. The main plots involved three irrigation intervals (two weeks, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…The reduction in cotton plant growth and metabolism was reflected by the lack of nutrients and cellulose to boll due to increased boll shedding and decreased cotton yield productivity compared to normal irrigation plants in both seasons (Table 9). A similar trend was indicated by Hamoda (2012) and Emara et al (2015), who showed that water-deficit conditions reduce stomatal conductance to water and CO 2 , the main reason for the decreased photosynthesis rate and plant growth and reduced cotton productivity. Also, Gomaa et al (2019) and Zaki & Radwan (2022) concluded that drought stress affects cotton plant hormonal imbalance (ABA), reducing plant growth and productivity.…”
Section: Effects Of the Main Factors And Their Interactions On The Yi...supporting
confidence: 83%
See 3 more Smart Citations
“…The reduction in cotton plant growth and metabolism was reflected by the lack of nutrients and cellulose to boll due to increased boll shedding and decreased cotton yield productivity compared to normal irrigation plants in both seasons (Table 9). A similar trend was indicated by Hamoda (2012) and Emara et al (2015), who showed that water-deficit conditions reduce stomatal conductance to water and CO 2 , the main reason for the decreased photosynthesis rate and plant growth and reduced cotton productivity. Also, Gomaa et al (2019) and Zaki & Radwan (2022) concluded that drought stress affects cotton plant hormonal imbalance (ABA), reducing plant growth and productivity.…”
Section: Effects Of the Main Factors And Their Interactions On The Yi...supporting
confidence: 83%
“…In contrast, the favorable effects of Ca in cotton yield components might be attributed to the important role in enhancing photosynthesis and maintaining turgor under drought stress conditions. Ca improves the water status of plants by enhancing the stability of membranes and protecting them from ROS-damaging effects (Emara et al, 2015;Ibrahim et al, 2016;More et al, 2018;Naeem et al, 2018). Ca acts as an anti-drought signaling response by participating in ABA-induced drought signal transduction, which enhances water use efficiency and opposes drought tolerance.…”
Section: Effects Of the Main Factors And Their Interactions On The Yi...mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, 120 and 150 kg ha −1 N supports a significant increase in plant height (Hallikeri et al, 2010; Kumbhar et al, 2008), and a high number of cotton nodes is achievable with 225 kg ha −1 of N application (Alitabar et al, 2013). At the same time, the mean internode length is also reported to be affected by the N uptake rate between 0 and 40 kg ha −1 (Emara & El‐Gammaal, 2012). In contrast, studies on N distribution in different parts of cotton during the vegetative growth periods propose efficient utilisation of N at lower rates of 84 kg ha −1 .…”
Section: Regulation Of N Allocation To Vegetative and Reproductive Br...mentioning
confidence: 99%